PENGARUH TRANSFORMASI LEADERSHIP TERHADAP FIRM PERFORMANCE DENGAN INNOVATION CAPABILITY DAN MANAGEMENT ACCOUNTING SYSTEM SEBAGAI MEDIASI - Kevin Faustina Safitri; Suci Atiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Transformational Leadership on firm performance with Innovation Capability and Management Accounting System as mediating. This research uses a quantitative approach with a survey method through the distribution of questionnaires to respondents involved in organizational activities. The collected data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results show that Transformational Leadership has a positive and significant effect on firm performance, innovation capability, and Management Accounting System.. Furthermore, the Management Accounting System has a positive and significant effect on firm performance, while Innovation Capability has a positive but not significant effect on firm performance. The mediation test results show that Innovation Capability does not mediate the relationship between Transformational Leadership and firm performance. In contrast, the Management Accounting System is proven to partially mediate the relationship.